A case report of multiple endocrine neoplasia type 1 and autoimmune disease: Coincidence or correlation?. Issue 49 (10th December 2021) - Chaves, Carolina; Nunes da Silva, Tiago; Dias Pereira, Bernardo; Anselmo, João; Claro, Isabel; Cavaco, Branca M.; Saramago, Ana; Leite, Valeriano
Abstract: Rationale: Multiple Endocrine Neoplasia type 1 (MEN1) is a familial syndrome that results from the disruption of a tumor suppressor protein called MENIN. Its management is challenging, as MEN1 affects different endocrine tissues and predisposes to both benign and malignant tumors. MENIN-deficient cells have recently been recognized to play a role in triggering autoimmunity. Herein, we present a case of MEN1 with multiple endocrine and autoimmune disorders. Patient concerns: A 50 years old female with a 25 years history of complicated nephrolithiasis presented with primary hyperparathyroidism. Diagnoses: Over several decades, she was diagnosed with recurrent primary hyperparathyroidism, autoimmune thyroiditis, multinodular goiter, pernicious anemia, metastatic gastric type 1 neuroendocrine tumor, macroprolactinemia, gonadotropin deficiency, mucosa-associated lymphoid tissue lymphoma of the thyroid gland, positive anti-calcium sensor receptor antibodies, and BRCA 1/2 -negative invasive breast cancer. The autoimmune regulator gene was sequenced, but no pathogenic variants were found. Next-generation sequencing revealed both a pathogenic MEN1 mutation and a benign CDC73 gene variant. Familial genetic screening revealed a large kindred with multiple carriers of one or both genetic variants ( MEN1 = 19; CDC73 = 7). Interventions: The patient underwent surgical excision of three parathyroid glands, total thyroidectomy and breast tumorectomy plus tamoxifen, and monthly injections of octreotide. The patient and family members with the MEN1 mutation are under a life-long surveillance program for MEN1 prototypic tumors. Outcomes: The patient was stable and alive during a 24-years follow-up period. Lessons: With the present case, the authors highlight a new interplay between MENIN and the immune system, which may have implications for future targeted life-long surveillance and treatment of MEN1 patients.